THE STRATEGY OF THE MADRASAH PRINCIPAL IN NEW STUDENT ADMISSIONS (PPDB): A STUDY AT MADRASAH ALIYAH MIFTAHUN NAJAH TANGKIT MUARO JAMBI - Samsu Samsu; Try Susanti; Tamsir Tamsir; Dewi Lestari (STKIP Pesisir Selatan, 2026)
This study aims to analyze the strategies employed by the principal in managing New Student Admissions (PPDB) at Madrasah Aliyah Miftahun Najah Tangkit, Sungai Gelam District, Muaro Jambi. The study employed a descriptive qualitative approach with a case study design. Data were collected through interviews, observations, and documentation. Data analysis consisted of data reduction, data display, and conclusion drawing. The findings revealed that the principal implemented six main strategies in managing the admission process, namely establishing a PPDB committee, setting student enrollment targets, conducting promotions through social media, distributing brochures and banners, utilizing akhirusanah activities as promotional media, and carrying out evaluations after the admission process. These strategies proved effective, as the number of enrolled students reached 95, exceeding the target of 90 students. The success of the admission process was supported by strong collaboration between the principal and the committee, a positive institutional reputation, community participation, and support from alumni and parents. However, several challenges were identified, including increasing competition among educational institutions, limited facilities and infrastructure, and a shortage of qualified teachers. This study highlights that the principal’s strategic leadership, supported by effective organizational communication and community involvement, plays a crucial role in enhancing the effectiveness of student admission management in pesantren-based madrasahs.